2014
DOI: 10.1111/jvim.12317
|View full text |Cite
|
Sign up to set email alerts
|

Breed Distribution of SOD1 Alleles Previously Associated with Canine Degenerative Myelopathy

Abstract: BackgroundPrevious reports associated 2 mutant SOD1 alleles (SOD1:c.118A and SOD1:c.52T) with degenerative myelopathy in 6 canine breeds. The distribution of these alleles in other breeds has not been reported.ObjectiveTo describe the distribution of SOD1:c.118A and SOD1:c.52T in 222 breeds.AnimalsDNA from 33,747 dogs was genotyped at SOD1:c.118, SOD1:c.52, or both. Spinal cord sections from 249 of these dogs were examined.MethodsRetrospective analysis of 35,359 previously determined genotypes at SOD1:c.118G>A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
100
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 19 publications
12
100
2
Order By: Relevance
“…The pathological features of DM are similar to the pathological features of ALS (17)(18)(19)(20)(21)(22). DM has been confirmed in over 24 breeds (16,23) and presumptively reported in another nine breeds (16). In a previous study of canine SOD1, a SOD1:c.118G > A transition was identified that leads to a nonsynonymous substitution (E40K) in the homologous codon to the human E40G mutation (17).…”
Section: Significancesupporting
confidence: 52%
See 4 more Smart Citations
“…The pathological features of DM are similar to the pathological features of ALS (17)(18)(19)(20)(21)(22). DM has been confirmed in over 24 breeds (16,23) and presumptively reported in another nine breeds (16). In a previous study of canine SOD1, a SOD1:c.118G > A transition was identified that leads to a nonsynonymous substitution (E40K) in the homologous codon to the human E40G mutation (17).…”
Section: Significancesupporting
confidence: 52%
“…Homozygosity for the variant allele was associated with risk of developing DM in five dog breeds (17). A separate SOD1 missense mutation has been discovered in Bernese Mountain Dogs, but has only been detected in that specific breed so far (23,24). Biochemical characterization of the two canine SOD1 mutant proteins indicated the increased propensity to form protein aggregates with retained enzymatic activity, supporting a toxic gain-of-function role in canine DM similar to that role in human ALS (25).…”
Section: Significancementioning
confidence: 89%
See 3 more Smart Citations